THE DEVELOPMENT OF ENGLISH LEARNING ACHIEVEMENT BY USING STAD COOPERATIVE LEARNING TECHNIQUE WITH ELECTRONIC BOOK OF GRADE 6 STUDENTS KEHACHUMCHONLADKRABANG SCHOOL - Thobmart, Wiluwee; Peanpedlerd, Surawee (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aims to 1) develop the achievement before and after learning of students by using STAD cooperative learning technique with electronic book and 2) examine the satisfaction of students with learning through using STAD cooperative learning technique with electronic book. The population of this study comprised 325 Grade 6 students enrolled in nine classes at Kehachumchonladkrabang School during the first semester of the academic year 2024. The sample consisted of 36 students from Grade 6 Class 7 derived from purposive selection. The research instruments included 1) lesson plans using STAD cooperative learning technique with electronic book 2) an achievement test on the English reading of Grade 6 students 3) a satisfaction survey form. Data analysis included mean scores, standard deviations, and t-test. The findings indicated that 1) E-BOOK has efficiency of 80.12/80.71 which is in line with efficiency of 80/80 and students who studied through STAD cooperative learning technique with electronic book had statistically higher learning achievement scores after learning at a significant level of .05. 2) The satisfaction of students with learning through STAD cooperative learning technique with electronic book was very satisfied.